Review of Substation Grounding System Behavior under High Frequency and Transient Faults in Uniform Soil - Permal N.; Osman M.; Kadir M.Z.A.A.; Ariffin A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fault currents; Electric substations; Design parameters; Electrical systems; Grounding systems; High frequency HF; Lightning strikes; Substation grounding systems; Switching transient; Transient conditions; Electric grounding